The phylogeny of nine species of the Drosophila obscura group inferred by the banding homologies of the chromosomal regions. IV. Element C - Brehm, António (2020)
Homologies of the sections of the polytene chromosomes of element C, among several species of the obscura group of the genus Drosophila, were established according to the similarity of their banding patterns. The information gathered was used to construct an unrooted phylogenetic tree based on qualitative criteria. This tree is compared to three other similar trees derived from independent information provided by the study of chromosomal elements B, D and E. The general congruence of the patterns of these trees proves the well-foundedness of this approach. A single exception to this congruence is discussed. Finally a consensus tree, encapsulating information from all chromosomal elements, is presented and its topology is compared to those derived from electrophoretic data.